Human and ihuman oppositions to the buffaloes of the Guaporé Valley – in Rondônia - Gonçalves, Marcus Fabiano; Oliveira, Terezinha Azevedo de; Santos, Anna Luíza Soares Diniz; Viana, Thiago da Silva (Seven Editora, 2024)
This article is a research that has the power to analyze the possibilities of the existence or not of human and legal impediments related to buffaloes in the Guaporé Valley, in Rondônia, and whether there is a link between the presence of these animals and regional environmental preservation. Thus, in this excerpt, it was investigated what is the correlation between buffalo breeding in this territory and the environmental maintenance of the region. The methodology applied was based on a survey of bibliographic references, questionnaires, and graphic demonstration of results to clarify the theses that were raised. And the work is justified by its thematic relevance since it enables a reflection on the benefit of preserving buffaloes in coexistence with humans. This is done in a weighing and analysis of the damage caused by man in the misuse of nature, with the devastation of forests, aquifers and its incident and serious consequences – such as the consequent energy crisis, dust clouds, the desertification of large areas and their rivers – arising as a result of this environmental imbalance: unemployment, increased poverty and hunger. DOI:https://doi.org/10.56238/sevened2024.007-006